Amalgamation of the Rarest: Homozygous Beta Thalassemia and Gilbert Syndrome - Kediya, Ayushi; Atreja, Charu Batra; Upadhyay, Meenal; Dhawan, Vishesh (Annals of Pathology and Laboratory Medicine, 2024)
Homozygous beta-thalassemia patients are known to show significant variability in serum unconjugated bilirubin levels, which can be attributed to the red cell destruction rate, ineffective erythropoiesis, or bilirubin elimination capacity. One cause of this hyperbilirubinemia is Gilbert syndrome ((TA)7/(TA)7 genotype), which is known to act as a modifying factor in thalassemic patients. Defective glucuronidation in Gilbert allele carriers aggravates jaundice in all hemolytic anemias, including thalassemia. Here, we present a rare case of the amalgamation of thalassemia intermedia and Gilbert syndrome in a young male patient.